The Role of Quality of Work Life Indicators in Developingthe Performance of Human Resources: A Case Study of Cable Industry Company - General Cable Branch – Biskra - عثمان مريم (Milev Journal of Research and Studies, 2023)
This study aimed to identify the role of the quality of work life indicators in developing the performance of human resources in Cable Industry Company - General Cable Branch– Biskra. To achieve the goal, the analytical descriptive approach was adopted; a questionnaire for the purpose of data collection, distributed to an intentional sample of (57) frameworks (employee, framework, manager, technician). The study concluded that there is a direct correlation and effect between the indicators of the quality of functional life (comfort at work, justice at work, physical conditions) &developing the performance of human resources.